Description of two new and two known species of the Genus Tylencholaimellus Cobb in M. V. Cobb, 1915 (Nematoda: Dorylaimida: Tylencholaimoidea) - Ahmad, Wasim; Ahad, Sumaya (Zootaxa, 2018)
Two new and two known species of the dorylaimid nematode genus Tylencholaimellus Cobb in M.V. Cobb, 1915 are described and illustrated. Tylencholaimellus arabicus sp. n. collected from Saudi Arabia is characterized by having small sized body (L= 0.66–0.83 mm); outer cuticle with distinct transverse striations; inner layer thick with fine transverse striations; lip region offset by a deep constriction, inner liplets slightly raised; odontostyle 15–17 µm, odontophore 8–10 µm, combined length 25–26 μm; female genital system mono-opisthodelphic; anterior uterine sac 0.5–1.3 times midbody diameter in length; transverse vulva and short conoid tail Tylencholaimellus masakii sp. n. collected from Japan is characterized by having small sized body (L= 0.77–0.81 mm); lip region offset by a slight constriction; labial disc present; odontostyle 11–12 µm, odontophore 6–7 µm, combined length 18–18.5 μm; female genital system mono-opisthodelphic; anterior uterine sac 1.1–1.8 midbody diameter long; transverse vulva and rounded-conoid tail. Tylencholaimellus striatus Thorne, 1939 and T. projectus Siddiqi, 1964 are redescribed based on material collected from India. A diagnostic compendium of the genus Tylencholaimellus is also provided.